KONTRIBUSI SYAIKH ABDUS SHAMAD AL-PALIMBANI PADA ASPEK INTELEKTUAL ISLAM DI NUSANTARA ABAD KE-18 - Arafah Pramasto (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2019)
Abstract : Sheikh Abdus Shamad Al-Palimbani’s Contributions toward Islam in 18th Century’s Indonesian Archipelago. Born in 1737 AD, Sheikh Abdus Shamad was a Sufi Ulema from Palembang.His grandfather, who was also a Sufi Ulema held a position of a Mufti in Kingdom of Kedah. His grandmother, however,belonged to a noble family from Sultanate of Palembang. Abdus Shamad received good education during his lifetime in Palembang.He later continued his journeyof knowledge-seekingby traveling to the Haramayn (Holy Lands of Islam) where he learned various Islamic principles. He also engaged in various discussions with Ulemas and Malay speaking diciples also called the Jawi Community.As an Ulema and an intellectual, Sheikh Abdus Shamad authored eight books mostly in the Malay language.Two magnum opus of his writings that gained popularity among Indonesian Muslims were Sufi-themed books i.e.Hidayatus Salikin fi Suluk Maslak al-Muttaqiin and Siyarus Salikin ila Ibadat rabb al-‘alamin.Keywords : Intellectual, Ulema, Indonesian Archipelago, Shaikh Abdus Shamad Al-PalimbaniAbstrak : Kontribusi Syaikh Abdus Shamad Al-Palimbani pada Aspek Intelektual Islam di Nusantara Abad ke-18. Syaikh Abdus Shamad Al-Palimbani merupakan seorang Ulama Sufi asal Palembang yang lahir pada tahun 1737 M. Secara genetis ia adalah keturunan Ulama Sufi (kakek) yang menjadi Mufti di Kerajaan Keddah dan bangsawan Kesultanan Palembang (nenek).Latar belakang keluarganya itu memberi andil bagi Abdus Shamad untuk memperoleh pendidikan yang baik selama di Palembang. Ia kemudian melanjutkan pendidikannya ke Haramayn (Tanah Suci) untuk belajar ilmu-ilmu agama kepada pada Ulama serta aktif terlibat diskusi keilmuan di dalam “Komunitas Jawi”, yakni orang-orang Nusantara berbahasa Melayu yang belajar di sana. Sebagai seorang Ulama sekaligus intelektual, Syaikh Abdus Shamad juga menghasilkan 8 buah karya yang sebagian besar berbahasa Melayu. Karyanya yang paling terkenal bagi Muslim di Nusantara adalah kitab Sufi berjudul Hidayatus Salikin fi Suluk Maslak al-Muttaqiin dan Siyarus Salikin ila Ibadat rabb al-‘alamin.Kata Kunci : Intelektual, Ulama, Nusantara, Syaikh Abdus Shamad Al-Palimbani